UPAYA PENINGKATAN KESEJAHTERAAN PETANI DI DESA BELOK SIDAN MELELUI KOPERASI PETANI BALI AGRO NUSANTARA - Budiarta, I Kadek Pandu; Nugroho, Wahyu Budi; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
This study analyzes and describes the efforts made by the Bali Agro Nusantara Farmer Cooperative in improving the welfare of farmers in Belok Sidan Village, and explains the impact of the cooperative for the village and Belok Sidan farmers. The method used in this research is qualitative descriptive explanative. As for the theory used in this research, the SWOT analysis method aims to see internal factors, namely the strengths and weaknesses that are owned in developing and technical guidance to cooperative members. As well as external factors, namely program weaknesses that are not yet owned and in terms of threats that will arise in organizational management. From the analysis and observations made by the researcher, it was found that the Bali Agro Nusantara Farmer Cooperative had more strengths and opportunities than weaknesses and threats. Keywords: Koperasi Bali Agro Nusantara, Belok Sidan farmer, Economic development.